2010
DOI: 10.1042/cbi20090025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vitro cytotoxicity of the antimicrobial peptide P34

Abstract: The in vitro cytotoxicity of the antimicrobial peptide P34 was evaluated in different eukaryotic cells. The food-grade bacteriocin nisin was also analysed for comparison. Vero cells were treated with different concentrations (0.02-2.5 microg x ml(-1)) of antimicrobial peptide P34 and nisin. Cell viability and plasma membrane integrity were checked by MTT [3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyltetrazolium bromide], NRU (Neutral Red dye uptake) and LDH (lactate dehydrogenase) assays. The EC50 values of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 42 publications
1
23
1
1
Order By: Relevance
“…Briefly, cells were incubated with serial dilutions (ranging from 0.31 to 100 g/ml) of either eCATH1, DEFA1, nisin, or 1% (vol/vol) Triton X-100 (positive control) for 24 h. Nisin was used here as a "safe control" because of its generally recognized as safe (GRAS) status in the food industry. The percentage of cytotoxicity was calculated as described by Vaucher et al (43). Each experiment was performed in triplicate, and values were expressed as mean Ϯ standard error.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, cells were incubated with serial dilutions (ranging from 0.31 to 100 g/ml) of either eCATH1, DEFA1, nisin, or 1% (vol/vol) Triton X-100 (positive control) for 24 h. Nisin was used here as a "safe control" because of its generally recognized as safe (GRAS) status in the food industry. The percentage of cytotoxicity was calculated as described by Vaucher et al (43). Each experiment was performed in triplicate, and values were expressed as mean Ϯ standard error.…”
Section: Methodsmentioning
confidence: 99%
“…Email: abrand@ufrgs.br Brandelli, 2008). A recent study indicates that peptide P34 had no adverse effects on eukaryotic cells, similarly to nisin, suggesting its potential as biopreservative (Vaucher, Motta, & Brandelli, 2010). Natamycin is a naturally occurring antifungal agent classified as a macrolide polyene, produced during fermentation by the bacterium Streptomyces natalensis.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial peptide P34 was isolated and characterized as a bacteriocin-like substance (BLS) by Motta et al (2007a) and the inhibitory activity was detected against Listeria monocytogenes, Bacillus cereus, and Salmonella Enteritidis (Motta et al 2007b. Furthermore, some studies showed low cytotoxicity in eukaryotic cells and antiviral activity against pathogenic virus of domestic animals (Vaucher et al 2010, Silva et al 2014.…”
mentioning
confidence: 99%